Social and Structural Determinants of Community Firearm Violence and Community Trauma. Issue 1 (November 2022) - Buggs, Shani A. L.; Kravitz-Wirtz, Nicole D.; Lund, Julia J.
The adverse impacts of community firearm violence in the U.S. are unequally felt across geographic and various sociodemographic segments of our population. Researchers, government leaders, and the general public need to contend with the various ways in which unjust socioeconomic and political forces and systems of power and privilege lead to differences in risk exposure among population groups, as well as differences in the extent to which various segments of the population are protected from the adverse effects of firearm violence. We highlight dozens of studies to illustrate how firearm violence and community trauma in the U.S. can be more effectively addressed when a "social and structural determinants" perspective is used to understand and respond to this public health problem.